2018
DOI: 10.1093/jac/dky447
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of antibiotic prescribing in the Emergency Department

Abstract: BackgroundAntibiotics are some of the most commonly prescribed drugs in the Emergency Department (ED) and yet data describing the overall appropriateness of antibiotic prescribing in the ED is scarce.ObjectivesTo describe the appropriateness of antibiotic prescribing in the ED.MethodsA retrospective, observational study of current practice. All patients who presented to the ED during the study period and were prescribed at least one antibiotic were included. Specialists from Infectious Disease, Microbiology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 37 publications
3
75
1
3
Order By: Relevance
“…Higher utilization of antibiotics in SOD was reported in previous published studies [9,10] and ED is an important setting for addressing antibiotic utilization, given that it sits at the interface of the community and the hospital [11,12]. Therefore, we selected SOD and ED, as these are important settings for addressing inappropriate antibiotic prescribing practices.…”
Section: Methodsmentioning
confidence: 96%
“…Higher utilization of antibiotics in SOD was reported in previous published studies [9,10] and ED is an important setting for addressing antibiotic utilization, given that it sits at the interface of the community and the hospital [11,12]. Therefore, we selected SOD and ED, as these are important settings for addressing inappropriate antibiotic prescribing practices.…”
Section: Methodsmentioning
confidence: 96%
“…A recent Australian study showed that over one in eight (13.6%) of all 7497 patients presenting during the study period received antibiotics in the ED. Of these, three‐quarters were given i.v., although fewer than 5% met qSOFA criteria for sepsis . A panel of experts found that over one in three of these were inappropriate.…”
Section: Introductionmentioning
confidence: 99%
“…If two or more assessors did not reach an agreement for any diagnosis code, then all six experts reviewed the case at a round table until a consensus was reached. The validity of this approach has been shown in previous studies [11,12]. Details of the discussion process to judge appropriateness of antibiotic prescription are available in Supplementary file 1.…”
Section: Assessment Of Appropriate Antibiotic Prescriptionmentioning
confidence: 76%